2014
DOI: 10.20333/25000136-2014-4-86-91
|View full text |Cite
|
Sign up to set email alerts
|

Components and Mechanisms of Forming the Learned Helplessness in Children With Weak Health: Ontogenetic Approach

Abstract: COMPONENTS AND MECHANISMS OF FORMING THE LEARNED HELPLESSNESS IN CHILDREN WITH WEAK HEALTH: ONTOGENETIC APPROACHO. V. Volkova Krasnoyarsk State Medical University named after Prof. V. F. Voyno-Yasenetsky Abstract. The article concerns the detailed theoretically-methodological analysis of the modern psychological researches devoted to studying of a "helplessness" phenomenon. The question of studying the relevance of "learned helplessness" phenomenon interrelation with somatic health of the person during formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Upon analysis of scientific literature, it was found that the potential of human personality characterises internal physical and spiritual energy of the person, his or her active position aimed at creative self-expression and self-realisation (Bennett, 2015;Bateson, 2016;Zubova, 2009;Volkova, 2014).…”
Section: State Of the Problemmentioning
confidence: 99%
“…Upon analysis of scientific literature, it was found that the potential of human personality characterises internal physical and spiritual energy of the person, his or her active position aimed at creative self-expression and self-realisation (Bennett, 2015;Bateson, 2016;Zubova, 2009;Volkova, 2014).…”
Section: State Of the Problemmentioning
confidence: 99%